2021
DOI: 10.3389/fnmol.2021.739016
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles in Serum and Central Nervous System Tissues Contain microRNA Signatures in Sporadic Amyotrophic Lateral Sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS) is a terminalneurodegenerative disease. Clinical and molecular observations suggest that ALS pathology originates at a single site and spreads in an organized and prion-like manner, possibly driven by extracellular vesicles. Extracellular vesicles (EVs) transfer cargo molecules associated with ALS pathogenesis, such as misfolded and aggregated proteins and dysregulated microRNAs (miRNAs). However, it is poorly understood whether altered levels of circulating extracellular ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 94 publications
1
37
2
Order By: Relevance
“…Although there are many biomarker studies on circulating miRNAs in ALS patients, exosomal miRNAs have been investigated in only a few studies with no overlapped results across studies. Likewise, the two validated miRNAs in present study, miR-192-5p and miR-23c, have not been identified in previous studies 17 22 . The inconsistency might be due to a combination of technical and biological factors including different methods for blood sample preparation (serum vs. plasma), EV isolation (precipitation, immuno- or peptide affinity, or a combination of both), miRNA profiling (microarray, RNA sequencing, NanoString), bioinformatic analysis, and biological variability along with disease heterogeneity.…”
Section: Discussioncontrasting
confidence: 72%
“…Although there are many biomarker studies on circulating miRNAs in ALS patients, exosomal miRNAs have been investigated in only a few studies with no overlapped results across studies. Likewise, the two validated miRNAs in present study, miR-192-5p and miR-23c, have not been identified in previous studies 17 22 . The inconsistency might be due to a combination of technical and biological factors including different methods for blood sample preparation (serum vs. plasma), EV isolation (precipitation, immuno- or peptide affinity, or a combination of both), miRNA profiling (microarray, RNA sequencing, NanoString), bioinformatic analysis, and biological variability along with disease heterogeneity.…”
Section: Discussioncontrasting
confidence: 72%
“…In fact, levels of the 14q32encoded miRNA miR-127-3p were altered in cells of this study as well as in the serum of sporadic and familial ALS patients in two previous studies. 98,99 In addition to biomarkers, miRNAs are also increasingly regarded as potential therapeutic targets, given that miRNAs can modulate hundreds of targets simultaneously. 100 In future work, individual miRNA mimics or synthetic miRNA clusters 101 may be employed to modulate levels of dysregulated miRNAs and their targets to assess phenotypic rescue.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs regulate posttranscriptional processing and may play a central role in regulating the spread of ALS pathology 57 . EVs are an optimal way to quantify miRNAs, as they reflect the state of the source cell from which the EV was derived, protect miRNAs from degradation via their phospholipid bilayer, and can pass through blood–CNS barriers due to their lipophilic nature 53,57,58 . While more research is needed to determine the exact miRNAs altered in ALS, multiple studies have demonstrated upregulated miR‐146a, miR‐151a, and miR‐3919‐3p and downregulated miR‐4454 and miR‐4286 56,57,59,60 .…”
Section: The Consequence Of Ev Propagation Of Als Pathology and Their...mentioning
confidence: 99%